Pengaruh Disiplin Kerja dan Perilaku Kerja Terhadap Kinerja Karyawan pada PTPN 1 Regional 1 Tanjung Morawa - Huzaini, Rofiqoh; Wahyuni, Neni Sri; Yusrita, Yusrita; Julkarnain, Julkarnain (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to determine partially and simultaneously the effect of work discipline and work behavior on employee performance at PTPN 1 Regional 1 Tanjung Morawa. This research method is quantitative. Data was collected through direct interviews and the distribution of questionnaires. The population consists of 222 employees, and the sampling technique is the Slovin formula with a standard error of 10%, so that the sample obtained is 69 people. This data analysis is a multiple linear regression analysis tested through SPSS. Based on the test results and analysis obtained, namely simultaneously, there is a positive and significant influence of work discipline and work behavior on employee performance at PTPN 1 Regional 1 Tanjung Morawa. Then, work discipline and work behavior each have a positive and significant effect on employee performance at PTPN 1 Regional 1 Tanjung Morawa.